2004
DOI: 10.1203/01.pdr.0000117847.59343.b2
|View full text |Cite
|
Sign up to set email alerts
|

Maternally Administered Dexamethasone at 0.7 of Gestation Suppresses Maternal and Fetal Pituitary and Adrenal Responses to Hypoxemia in Sheep

Abstract: Women who are at risk of preterm delivery are treated with antenatal steroids to facilitate fetal lung maturation. During this period, there is a potential for fetal or maternal hypoxemia to occur. Fetal responses to hypoxemia in sheep are well documented. However, less is known regarding maternal responses to hypoxemia. Therefore, we determined the effects of dexamethasone (DM) on maternal and fetal responses to hypoxemia in sheep. Ewes received four i.m. injections of DM or saline at 12-h intervals beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Dexamethasone, which readily crosses the placenta, binds to glucocorticoid receptors (GR) in the fetal pituitary, hypothalamus and hippocampus, thereby decreasing negative feedback of the HPA pathway leading to low cortisol concentrations (Bertram and Hanson 2002). Suppression of cortisol, or blunted adrenal responses, also occurs in offspring of other species following maternal glucocorticoid treatment (Kutzler et al 2004;Davis et al 2006;Kranendonk et al 2006). In the present study, attenuated adrenocortical function may also have contributed to the lethargy observed in one of the foals and could have implications for the use of dexamethasone in a clinical setting (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexamethasone, which readily crosses the placenta, binds to glucocorticoid receptors (GR) in the fetal pituitary, hypothalamus and hippocampus, thereby decreasing negative feedback of the HPA pathway leading to low cortisol concentrations (Bertram and Hanson 2002). Suppression of cortisol, or blunted adrenal responses, also occurs in offspring of other species following maternal glucocorticoid treatment (Kutzler et al 2004;Davis et al 2006;Kranendonk et al 2006). In the present study, attenuated adrenocortical function may also have contributed to the lethargy observed in one of the foals and could have implications for the use of dexamethasone in a clinical setting (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone, which readily crosses the placenta, binds to glucocorticoid receptors (GR) in the fetal pituitary, hypothalamus and hippocampus, thereby decreasing negative feedback of the HPA pathway leading to low cortisol concentrations (Bertram and Hanson 2002). Suppression of cortisol, or blunted adrenal responses, also occurs in offspring of other species following maternal glucocorticoid treatment (Kutzler et al . 2004; Davis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Because rodents are typically viewed as 'corticoid-sensitive' species, and their newborn pups are extremely immature at birth, the immediate relevance of the rat and mouse models has sometimes been questioned. However, similar types of adverse effects, including an influence of physical growth and suppression of maternal and fetal adrenal activity, have also been observed in sheep [8,39,40]. The alterations in sheep are a little more surprising because high maternal cortisol levels play such an important role in the normal physiology of their pregnancy and parturition.…”
Section: Conclusion and Implications Of The Monkey Studiesmentioning
confidence: 94%
“…Circulating concentrations of cortisol in the human and in other species, such as the sheep, are naturally increased in the latter half of pregnancy 65 67 . Stress, as previously discussed, further elevates the concentration of cortisol 68 , 69 . But the fact that the normal set point for cortisol is increased in pregnancy raises the question of why this occurs and whether there are species differences with regard to mechanism 68 .…”
mentioning
confidence: 65%